Inhibition of BMP activity protects epithelial barrier function in lung injury. Issue 1 (10th July 2013) - Helbing, Thomas; Herold, Eva‐Maria; Hornstein, Alexandra; Wintrich, Stefanie; Heinke, Jennifer; Grundmann, Sebastian; Patterson, Cam; Bode, Christoph; Moser, Martin
Abstract: Epithelial injury is a central finding in pulmonary disease and is accompanied by disruption of epithelial barrier function, leading to pulmonary oedema and inflammation. Injured epithelial cells lose their properties and gain mesenchymal characteristics, a phenotypic switch that contributes to lung remodelling after injury. Here we studied bone morphogenetic protein (BMP) signalling and, in particular, the role of BMP2 and the BMP modulator BMPER in injured lung epithelium. Increased BMP activity, reflected by up‐regulation of the Smad1/5–Id1 axis, is detected after injury of lung epithelium in vitro and in vivo . Two members of the BMP family, BMP2 and BMPER, have opposing effects. BMP2 is up‐regulated after epithelial injury and causes epithelial dysfunction and hyperpermeability, mediated by the Smad1/5–Id1‐dependent down‐regulation of E‐cadherin. In contrast, BMPER expression is decreased following injury, which in turn impairs epithelial integrity, characterized by reduction of E‐cadherin and epithelial leakage in vitro and in vivo . High levels of BMPER antagonized BMP2‐Smad5–Id1 signalling and prevented BMP2‐mediated decrease of E‐cadherin and hyperpermeability, suggesting that BMPER restores epithelial homeostasis. Supporting this notion, pharmacological inhibition of BMP signalling by LDN193189 prevented reduction of E‐cadherin and disruption of epithelial barrier function. Inhibition of excessive BMP activation could be a new approach to restore epithelial integrity and prevent disruption of epithelial barrier function after lung injury. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.